Characterization and risk stratification of prostate cancer in patients undergoing radical cystoprostatectomy - Buse, Stephan; Höfner, Thomas; Müller, Stephan C.; Hermann, Edwin; Wieland, W.; May, Matthias; Stief, Christian Georg; Bastian, Patrick J.; Hohenfellner, Markus; Haferkamp, Axel (International journal of urology, 2013)
To describe the prevalence of incidental prostate cancer in patients undergoing radical cystoprostatectomy for bladder malignancy; to quantify the association between incidental prostate cancer and mortality in these patients; and to quantify the association between incidental prostate cancer and age in radical cystoprostatectomy specimens.
Gesehen am 11.12.2020